2011
DOI: 10.1103/physrevlett.106.084501
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Basset-Boussinesq-Oseen Equation for Unsteady Forces on a Sphere in a Compressible Flow

Abstract: Viscous compressible flow around a sphere is considered in the limit of zero Reynolds and Mach numbers. An exact expression for the force on the sphere undergoing arbitrary motion with compressibility effects is presented. Quasisteady, inviscid-unsteady, and viscous-unsteady force components are identified. Numerical results are in excellent agreement with the theory. The present formulation offers an explicit expression for the unsteady force in the time domain and can be considered as a generalization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…Several early authors performed analytical studies of Stokes flow over bodies accelerating in incompressible viscous flow at low Reynolds numbers, deriving the force on a sphere and an expression for the boundary layer. This led to the formulation of the Basset-Bousinessq-Oseen equation for the motion of a particle in the limit of low Mach and Reynolds numbers and its subsequent extension to compressible flow [11]. The terms Bousinessq-Basset force, Basset force [12] or history force refer to the fact that the development of a boundary layer over an accelerating particle in a fluid depends on the temporal history of the fluid near the particle surface.…”
Section: Earlier Workmentioning
confidence: 99%
“…Several early authors performed analytical studies of Stokes flow over bodies accelerating in incompressible viscous flow at low Reynolds numbers, deriving the force on a sphere and an expression for the boundary layer. This led to the formulation of the Basset-Bousinessq-Oseen equation for the motion of a particle in the limit of low Mach and Reynolds numbers and its subsequent extension to compressible flow [11]. The terms Bousinessq-Basset force, Basset force [12] or history force refer to the fact that the development of a boundary layer over an accelerating particle in a fluid depends on the temporal history of the fluid near the particle surface.…”
Section: Earlier Workmentioning
confidence: 99%
“…[19,20]. For a compressible now, the dependence of the added-mass force on the instantaneous relative acceleration is no longer valid [21][22][23]. Due to the finite speed of the propagation of sound, the added-mass force depends on the history of the particle relative acceleration and is expressed in an integral form.…”
Section: Introductionmentioning
confidence: 98%
“…27,28 The detailed model for particles in a compressible flow has been developed recently. [29][30][31] It has also been shown that for certain particle parameters, the point-particle model can still be used to study the particle-shock interaction. 32 In this study, we will investigate inertial particles with different density advected in a compressible homogeneous isotropic turbulence by using numerical simulations.…”
mentioning
confidence: 99%
“…For finite size sphere interacting with a shock, the force experienced by the sphere has been discussed in detail. 29,30 Here, we shall assume point particle and employ a simple model to explain the behavior of v n . Starting from Eq.…”
mentioning
confidence: 99%